The convergence of distance and conventional education : patterns of flexibility for the individual learner - Tait, Alan; Mills, Roger, 1941- (Routledge studies in distance education., 2002)
This book focuses on the convergence of open and distance learning approaches with conventional education, driven to a considerable extent by a range of technologies which support learning and which are being adopted in all sectors.